The Role of Notaries in Making Wills Regarding the Distribution of Inheritance according to Islamic Compilation Law - Nirwan Kusuma; Aryani Witasari; Denny Suwondo (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This research aims to know and analyzing the role of a notary in making a will regarding the distribution of inheritance according to Islamic law.Analyzing the role of a Notary in making a will based on the provisions of the laws and regulations in force in Indonesia as well as the compilation of Islamic law as well as the obstacles and solutions of a notary inmaking a will regarding the distribution of inheritance according to Islamic law. This research is a type of legal research with a focus on the study of sociological juridical approach (Sociology Legal Research). Juridically by reviewing the applicable laws and regulations in accordance with the compilation of Islamic law and the Civil Code to achieve the final goal. The results of a sociological juridical study on the role of the role of a notary in making a will regarding the distribution of inheritance according to Islamic law is the role of a Notary in making a will before a Notary refers to the provisions of Article 1 point 1 UUJN which states,